TERM AL-KAUTSAR DALAM TAFSIR: STUDI KOMPARATIFTAFSIR MAHASIN AL-TA’WIL, AL-MIZAN, DAN SAFINAH KALLA SAYA’LAMUN - Muhamad Agus Efendi; Widia Duwi Putri (Yayasan Baitul Hikmah al-Zain, 2024)
The majority of mufassirs who interpret the term al-kautsar place the meaning of al-kautsar as 'descendants' of the Prophet Muhammad in the position of qoul (opinion), but on the contrary al-Qasimi, al-Thabathabai, and Maemoen Zubair favor the meaning as the main meaning. Although written based on three different ideologies, the three books of tafsir have the same interpretation of the term al-Kautsar in the Qur'an. This study aims to compare the interpretation of the term al-Kautsar in Tafsir Mahasin at-Ta'wil, Tafsir al-Mizan, and Tafsir Kalla Saya'lamun. This research is descriptive qualitative by using literature study method. This study shows that there are similarities and differences in interpretation between Jamaluddin al-Qasimi, Muhammad Hussein al-Thabathaba'i, and Maemoen Zubair on the term al-kautsar in Surah al-Kautsar. The similarity of the three interpretations is in the dimension of the text based on asbabun nuzul on the meaning of descent in the term al-Kautsar, while the difference between the three interpretations is in the sources used to strengthen the arguments of each interpretation.